The Gender Gap in Aversion to COVID-19 Exposure: Evidence from Professional Tennis - Zuzanna Kowalik; Piotr Lewandowski (Institute of Labor Economics (IZA), 2020)
We study the gender differences in aversion to COVID-19 exposure. We use a natural experiment of the 2020 US Open, which was organized in the country with the highest number of COVID-19 cases and deaths, and was the first major professional tennis tournament that was held after the season had been paused for six months. We analyze the gender gap in the propensity to voluntarily withdraw because of COVID-19 concerns among players who were eligible and fit to play. We find that female players were significantly more likely than male players to have withdrawn from the 2020 US Open. While players from countries characterized by relatively high levels of trust and patience and relatively low levels of risk-taking were more likely to have withdrawn than their counterparts from other countries, female players exhibited significantly higher levels of aversion to pandemic exposure than male players even after cross-country differences in preferences are accounted for. About 15% of the probability of withdrawing that is explained by our model can be attributed to gender.
Keywords: J16; I12; J44; 330; COVID-19; exposure to disease; gender; aversion; tennis